An Analysis of Metadiscourse and Pragmatic Hedges in Fred Rogers’ Commencement Speech - Intan Mustika Sari (Langkawi: Journal of The Association for Arabic and English, 2023)
The research on metadiscourse formerly examined the language tools used to construct a speech without looking further at the contextual-related resource. This study aims to investigate the textual and interpersonal meanings of Fred Rogers' commencement speech in Hyland's metadiscourse by examining interactive and interactional metadiscourse resources combined with Salager-Meyer's pragmatic hedges categorization. This present qualitative study adopted Bogdan et al. (1975) research design. The data were taken from Marquette University website on April 9th, 2022, and validated through documentation and audit trails. Afterward, they were identified and analyzed using Hyland's metadiscourse and Salager-Meyer pragmatic hedges framework in the interactive data analysis model proposed by Miles and Huberman which consists of data reduction, data display, and conclusion. The results revealed that self-mentions are the most significant interactional resource, reaching 47.39% of the total metadiscourse found in Fred Rogers' speech, and 30.33% are transition markers from interactive resources. In addition, the most significant hedge categories are shields and approximators that share the same accumulation at 35.29%. It showed that most words represent the speaker's intention to attract the audience's attention and emphasize his message by portraying the speaker's identity, attitude, and personal doubt. These results contribute to an understanding of metadiscourse markers and pragmatic hedges used for involving the speaker as the major constructor of discourse produced through the selection of markers in his utterances. The implications of this study can be a reference in selecting the linguistic markers to build effective communication for engaging the audience through discourse.